MODELS AND MODELLING IN CHEMISTRY EDUCATION IN THE HIGHER MEDICAL EDUCATION SYSTEM - Vasil Hadzhiiliev (Science & Research)

(untitled)
The objective of this paper is to consider the "classical" forms of training in higher medical school and try to give a new reading of the organizational forms of training, updated by the modern requirements addressed to the higher education institutions in Bulgaria, after adoption of the credit accumulation and transfer system. The compulsory training, which meets the requirements of the MILC, shall be conditionally made module A. Under this module, students attend both forms of training – lectures and practical exercises. The second group of activities builds on the knowledge and skills to be included in module C. This activity is built only on a type A activity already carried out, including free-elective and optional preparation in Chemistry. The formation of scientific competencies is carried out through direct scientific work, including literature review, searching for a suitable methodology for work, drawing up an experimental plan, reporting and analyzing the results of a real experiment (module C). This activity builds on the previous two and includes elements of reproduction and creativity.